Dynamics of Political Contestation in the Tangerang Regency Pilkada: Reflections on the Quality of Local Democracy - Rery, Faradila Kamila; Muslim, Jaliludin (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2025)
This study explores the dynamics of political contestation in the Regional Head Election (Pilkada) of Tangerang Regency, with a focus on political participation, the role of political parties in democratic processes, and the competition among candidates in local political arenas. The primary aim is to analyze how these dynamics reflect the quality of democracy at the local level and to identify key challenges, including social issues that emerge throughout the election process. Employing a qualitative approach through literature study, the research draws on a range of relevant scholarly sources. The findings indicate that political contestation in the Tangerang Regency Pilkada significantly influences the trajectory of local democratic development. Political parties play a pivotal role in building coalitions and nominating candidates, often adopting a pragmatic strategy that prioritizes electoral success over ideological consistency. This reflects a transformation in the nature of local democratic engagement, where the public shifts from being passive recipients to active participants in shaping political leadership.